Comparison of Minisatellite Polymorphisms in the Bacillus cereus Complex: a Simple Assay for Large-Scale Screening and Identification of Strains Most Closely Related to Bacillus anthracis - Valjevac, Samina (American Society for Microbiology, 2005)
Polymorphism of five tandem repeats that are monomorphic in Bacillus anthracis was investigated in 230 isolates of the B. cereus group and in 5 sequenced B. cereus genomes in search for markers allowing identification of B. cereus and B. thuringiensis strains most closely related to B. anthracis. Using this multiple-locus variable number of tandem repeat analysis (MLVA), a cluster of 30 strains was selected for further characterization. Eventually, six of these were characterized by multilocus sequence type analysis. One of the strains is only six point mutations (of almost 3,000 bp) away from B. anthracis and was also proposed to be closest to B. anthracis by MLVA analysis. However, this strain remains separated from B. anthracis by a number of significant genetic events observed in B. anthracis, including the loss of the hemolysin activity, the presence of four prophages, and the presence of the two virulence plasmids, pXO1 and pXO2. One particular minisatellite marker provides an efficient assay to identify the subset of B. cereus and B. thuringiensis strains closely related to B. anthracis. Based on these results, a very simple assay is proposed that allows the screening of hundreds of strains from the B. cereus complex, with modest equipment and at a low cost, to eventually fill the gap with B. anthracis and better understand the origin and making of this dangerous pathogen.